Histopathological study of Non-neoplastic & Neoplastic ovarian lesions in a tertiary care hospital in Gujarat, India - Dr. Alpesh M Maru; Dr. Chiragkumar B. Menapara (Tropical Journal of Pathology and Microbiology, 2019)
Aims & Objectives:(1) To know about various histopathological types of ovarian lesions presented and diagnosed at our institute. (2) To study the incidence of ovarian lesions with respect to patient’s age. (3) To study the frequency of ovarian lesions in terms of non-neoplastic or neoplastic, benign or malignant, unilateral or bilateral, etc. Materials & Methods: The present study was performed at the Department of Pathology, GMERS Medical College & Hospital-Junagadh (Gujarat, India) from January 2015 to December 2018 and includes 100 cases of ovarian lesions diagnosed on both clinical & histopathological basis. We have received ovarian specimens and performed routine grossing and H& E staining procedure. We have included parameters like Age wise incidence, Nature of Lesion, Frequency & Laterality in this present study. Results: Out of100 cases, 89% are unilateral and 11% are bilateral. 52% lesions are Benign Neoplasms, 44% lesions are Non-neoplastic Cysts and 4% lesions are Borderline & Malignant Neoplasms. Majority of cases (58%) belong to age group of 20-39 years. Among Non-neoplastic Lesions, Follicular Cyst is common & frequently bilateral while among Benign Neoplasms, Serous Cystadenoma is common & frequently bilateral. Conclusion: Ovarian Lesions both non-neoplastic and neoplastic include a variety of morphological features and show a particular age wise incidence. Role of histopathological evaluation remains always important in both diagnosis & management of such cases, particularly in cases of Malignant Lesions in order to save the patient’s life.